Analisis Penggunaan Energi Listrik di Gedung Instalasi Bedah Sentral dan Perawatan Intensif - Slamet Nurhadi; Heri Sungkowo; Nunun Setyo Nadia Putri (UPT - P2M POLINEMA, 2022)
Energy audit is a technique for calculating Energy Consumption Intensity (IKE) and aims to determine the energy use profile of a building and seek efforts to increase energy efficiency without reducing the comfort level of the building. The analytical method used is to make observations at Waluyo Jati Hospital by measuring the building area and ensuring appropriate lighting. Based on the Initial Energy Audit (AEA) which has been calculated and measured, the value of the intensity of energy has not met the standard because it is below the IKE standard for hospitals, which is 32.90617486 kWh/m2 on account calculations and 31.51399876 kWh /m2 on measurements that have been made, while the hospital IKE standard is 380 kWh/m2. The lighting system in the building still does not meet the standard of lighting strength according to the Regulation of the Minister of Health of the Republic of Indonesia No. 7 of 2019 concerning hospital environmental health. And for the lighting system it is not optimal and efficient, where the power consumption before repair according to the calculation is 4343.04 kWh, while after repair it becomes 4181.76 kWh / month 4343.04 kWh. The way to make energy use more efficient is to utilize natural light from the sun and change lamps and install energy-saving stickers in every corner of the room in the Central Surgical Installation and Intensive Care building at Waluyo Jati Kraksaan Hospital